2017
DOI: 10.2105/ajph.2017.303668
|View full text |Cite
|
Sign up to set email alerts
|

Jail Booking as an Occasion for HIV Care Reengagement: A Surveillance-Based Study

Abstract: Incarcerated PLWHA are disproportionately virally nonsuppressed compared with nonincarcerated PLWHA up to a year after release from jail. Public Health Implications. Coordination of health information exchange between the health department and jails could enhance public health efforts to improve the HIV care continuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Thirty (71%) of the studies were from high-income countries; USA (18), Canada (5) and Europe (7) while the remaining twelve (29%) were from low-and middle-income countries; Asia (5), sub-Saharan Africa (5) and Latin America (2). 41% (17) of the studies were cross-sectional [5,11,16,23,25,26,[45][46][47][48][49][50][51][52][53][54][55], 38% (16) cohort (14 retrospective and 2 prospective) [4,9,15,17,[19][20][21][56][57][58][59][60][61][62][63][64] and 19% (8) qualitative [12-14, 28, 65-68] in study design. One study employed mixed methods [22].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty (71%) of the studies were from high-income countries; USA (18), Canada (5) and Europe (7) while the remaining twelve (29%) were from low-and middle-income countries; Asia (5), sub-Saharan Africa (5) and Latin America (2). 41% (17) of the studies were cross-sectional [5,11,16,23,25,26,[45][46][47][48][49][50][51][52][53][54][55], 38% (16) cohort (14 retrospective and 2 prospective) [4,9,15,17,[19][20][21][56][57][58][59][60][61][62][63][64] and 19% (8) qualitative [12-14, 28, 65-68] in study design. One study employed mixed methods [22].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study employed mixed methods [22]. Fifteen studies reported on linkage to HIV care or ART initiation or both [5, 9, 11, 12, 22, 23, 45-50, 55, 65, 66] (Table 1), sixteen on adherence [12-15, 17, 20, 25, 26, 28, 45, 51, 52, 55, 56, 67, 68] (Table 2) and twenty on CD4 count or viral load or both [4,5,16,17,19,21,23,25,51,53,54,[56][57][58][59][60][61][62][63][64] (Table 3). Nine studies reported more than one element of the HIV care cascade and hence were included in more than one category [5,12,17,23,25,45,51,55,56].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile testing has been employed to reach individuals in a wide range of high-risk settings, providing flexibility in testing sites and populations targeted [61]. HIV testing in jails and prisons is high yield for new diagnoses and frequently offers an opportunity for re-engagement [75, 76]. While universal screening in jails and prisons would be ideal, it is not always feasible; thus studies evaluating the relationship between arrest charge and HIV risk are promising to efficiently target testing [77].…”
Section: Care Continuum Entry Interventionsmentioning
confidence: 99%
“…The HIV epidemic disproportionately affects the incarcerated population in the US, with a 1.3% seroprevalence that is approximately three times that of the general population [1]. Furthermore, compared to people living with HIV (PLH) in the US general population, incarcerated PLH are often less likely to have achieved HIV care continuum milestones [2,3] -engaged in care, received and adhered to antiretroviral therapy (ART) and achieved virologic suppression -at the time of incarceration [4][5][6][7]. The disproportionate burden as well as the profound challenges in achieving the care continuum reflect how the incarcerated population represents one of the most socially and economically marginalized individuals in the US [8][9][10].…”
Section: Introductionmentioning
confidence: 99%